Fundamentalist ; Smoke belching ; Willem Dafoe [videorecording] - Laaro, Cheche (Quezon City Probe Productions, 1989)
Deals with the feud between Catholic church and the Bible Christians or Fundamentalists ; discusses the perrenial problems of smoke belchers in the metropolis ; and the interview with Hollywood actor, Willem Dafoe.
Fundamentalist (15min.) -- Smoke belching (16 min.) -- Willem Dafoe (15 min.)
VHS.
Keywords: Dafoe, Willem -- Interviews; Religions; Fundamentalism -- Philippines; Smoke prevention -- Philippines -- Manila Metropolitan area; Air-pollution -- Philippines -- Manila Metropolitan area; Motion pictures -- Censorship. -- Philippines; Modernist fundamentalist controversy